2006
DOI: 10.1007/s00442-006-0405-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative strengths of benthic algal nutrient and grazer limitation along a lake productivity gradient

Abstract: The relative effects of nutrients and herbivores on primary producers are rarely compared across ecosystems that vary in potential primary productivity. Furthermore, proposed mechanisms to explain such patterns remain understudied. Here, I examine the strength of nutrient and grazer (herbivore) limitation (i.e., the extent to which producers' growth is limited by insufficient nutrient supply or herbivory) of benthic algae across 13 southwest Michigan lakes that vary widely in productivity (i.e., resource suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
(76 reference statements)
2
4
0
Order By: Relevance
“…The interactive effects of light and nutrients appeared to switch on at a riparian reserve width of 10‐m, which corresponds to a light flux of about 75 μmol m −2 s −1 . This result is qualitatively similar to studies in stream, lake, marine, and terrestrial systems that found nutrients interact with ambient environmental conditions to influence plant growth (Rosemond 1993, Wootton et al 1996, D'Antonio et al 2001, Brewer 2003, Darcy‐Hall 2006). For example, Taulbee et al (2005) found that primary producer biomass increased as light levels increased but only on nitrogen‐enriched substrates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The interactive effects of light and nutrients appeared to switch on at a riparian reserve width of 10‐m, which corresponds to a light flux of about 75 μmol m −2 s −1 . This result is qualitatively similar to studies in stream, lake, marine, and terrestrial systems that found nutrients interact with ambient environmental conditions to influence plant growth (Rosemond 1993, Wootton et al 1996, D'Antonio et al 2001, Brewer 2003, Darcy‐Hall 2006). For example, Taulbee et al (2005) found that primary producer biomass increased as light levels increased but only on nitrogen‐enriched substrates.…”
Section: Discussionsupporting
confidence: 87%
“…Resource supply and predation pressure vary within and among natural systems, likely contributing to the relative importance of these factors in shaping trophic level biomass and abundance. It is logistically difficult to manipulate more than one ecological gradient simultaneously, but such experiments are critical if we are to have any confidence in predicting the effects of environmental change on community structure or ecosystem function (Hunter and Price 1992, Chase 2003, Darcy‐Hall 2006). I describe results from a study that examined the main and interactive effects of light, nutrients and predator abundance in affecting primary producers and consumers.…”
mentioning
confidence: 99%
“…It has been suggested that a substantial part of the photosynthesis in clear-water lakes occurs in benthic algal communities, and the fraction of benthic productivity that is transferred to consumers decreases as the amount of dissolved carbon increases in the water column [14]. Consequently, changes in light abundances due to dissolved colored carbon can weaken the strength of trophic interactions by limiting the productivity of basal trophic levels [37], as we observed even in high nutrient conditions. This result highlights that mild nutrient loads that can increase the relative importance of predators' indirect effects on basal trophic levels [10] may be diminished in dark-water lakes.…”
Section: Discussionsupporting
confidence: 53%
“…Herbivory may also play an important role regulating periphytic algal biomass, although not measured in this experiment. However, experimental studies conducted with benthic algal communities showed that grazer limitation is weak compared with nutrient limitation at low productivity sites (Darcy-Hall 2006). Thus, grazer regulation of benthic algal biomass is expected to be weak in this experiment.…”
Section: Discussionmentioning
confidence: 93%